BIOMONITORING OF A FRESHWATER HABITAT OF RANCHI (HATIA DAM) ON THE BASIS OF NYGAARD’S INDICES - LATIKA SHARAN; REKHA SINHA (The Bioscan, 2010)
The paper deals with evaluation of the trophic status of a freshwater habitat of Ranchi (Hatia Dam) on the basis of year round qualitative and quantitative investigation of microphytic community and calculation of Myxophycean, Chlorophycean, Diatom and Compound indices of Nygaard. The values of all the indices indicated that the water body is oligotrophic. The Myxophycean and Chlorophycean indices varied from 0.020 to 0.400 while Diatom index ranged from 0.20 to 0.66 and Compound index showed the variation from 0.102 to 1.200.